Development and Assessment of Novel Multiligament Knee Injury Reconstruction Graft Constructs and Techniques - Cook, James L.; Cook, Cristi R.; Bozynski, Chantelle C.; Bezold, Will A.; Stannard, James P. (The Journal of Knee Surgery, 2020)
Multiligament knee injury (MLKI) typically requires surgical reconstruction to achieve the optimal outcomes for patients. Revision and failure rates after surgical reconstruction for MLKI can be as high as 40%, suggesting the need for improvements in graft constructs and implantation techniques. This study assessed novel graft constructs and surgical implantation and fixation techniques for anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), posterior medial corner (PMC), and posterior lateral corner (PLC) reconstruction. Study objectives were (1) to describe each construct and technique in detail, and (2) to optimize MLKI reconstruction surgical techniques using these constructs so as to consistently implant grafts in correct anatomical locations while preserving bone stock and minimizing overlap. Cadaveric knees (n = 3) were instrumented to perform arthroscopic-assisted and open surgical creation of sockets and tunnels for all components of MLKI reconstruction using our novel techniques. Sockets and tunnels with potential for overlap were identified and assessed to measure the minimum distances between them using gross, computed tomographic, and finite element analysis-based measurements. Percentage of bone volume spared for each knee was also calculated. Femoral PLC-lateral collateral ligament and femoral PMC sockets, as well as tibial PCL and tibial PMC posterior oblique ligament sockets, were at high risk for overlap. Femoral ACL and femoral PLC lateral collateral ligament sockets and tibial popliteal tendon and tibial posterior oblique ligament sockets were at moderate risk for overlap. However, with careful planning based on awareness of at-risk MLKI graft combinations in conjunction with protection of the socket/tunnel and trajectory adjustment using fluoroscopic guidance, the novel constructs and techniques allow for consistent surgical reconstruction of all major ligaments in MLKIs such that socket and tunnel overlap can be consistently avoided. As such, the potential advantages of the constructs, including improved graft-to-bone integration, capabilities for sequential tensioning of the graft, and bone sparing effects, can be implemented.
Keywords: multiligament knee injury; anterior cruciate ligament; graft constructs; surgical technique; socket and tunnel overlap